AN OVERVIEW ON TUBULARCULOSIS TREATMENT IN CURRENT SCENARIO - BUDHORI, AMIT; TIWARI, ABHISHEK; TIWARI, VARSHA; KUMAR, MANISH (Asian Journal of Pharmaceutical and Clinical Research, 2020)
The causative agent of tuberculosis (TB) is Mycobacterium tuberculosis, which mainly infects lungs and causes severe, fever, weight loss, chest pain, etc. It is an extremely transmittable disease spreaded throughout the world as per the WHO. It has emerged as new threat and drug resistance strains of Mycobacterium are emerging throws a challenge to human’s health like Covid-19 in current scenario. TB is now come in the form of bone TB, which is very difficult to diagnosis due to very slow-growing characteristics of Mycobacterium. This review highlights the history, drug development, current treatment both allopathic and Ayurvedic, as well as novel drugs available for the treatment of drug resistance Mycobacterium.